PENGARUH MODEL ATI BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Komang Merdana Ariasa (Universitas Pendidikan Ganesha, 2018)
This study used quasi experiment research through post test which only used control group design. This study tried to experiment Aptitude Treatment Interaction (ATI) model assisted audio visual media aimed to know the effect on science learning outcomes in grade V elementary students in Group IV Cempaka Putih Kecamatan Kubutambahan. The population of this study were the entire students of grade V in group IV Cempaka Putih, which amount to 168 students. The sample of this research were class V SDN 2 and 3 Bulian with the number of each students were 25 and 2, which was determined by random sampling technique. The data were analyzed by descriptive statistic and Independent Sample t-test. The results showed that the value of t count of 2.025 and ttab of 2.00. It meant that there was a significant effect of science learning outcomes between groups of students who were taught by ATI model assisted audio visual media and groups of students who were taught by non-ATI assisted by audio visual media.